Optimal Inflation Threshold for Economic Growth in Malawi - Nkume, Jean-Baptiste (Journal of Economics and Behavioral Studies, 2014)
There is near consensus in the literature that high levels of inflation (above 40%) affect economic growth negatively. The effects of low and moderate inflation, however, are ambiguous. Nonetheless, several studies have found that low levels of inflation are positively correlated with economic growth, which suggests the existence of a curvilinear relationship between inflation and economic growth. This study sets out to find the threshold level of inflation that is consistent with optimal and sustainable economic growth in Malawi. Using annual time series data for the period 1980 to 2013 and the Conditional Least Squares method, the study finds an optimal inflation threshold level of 17 percent for the country. The study results show that gains in real GDP growth below the optimal threshold level are greater than gains above the threshold level, which is consistent with the theoretical expectations of the threshold estimation model and other empirical studies. Unlike similar optimal inflation threshold studies, this study carries out structural change tests (using the Vogelsang approach) prior to estimating the threshold model. The data are also tested for unit roots using the Zivot and Andrews test for unit roots with a single structural break, and the Lumsdaine and Papell test for unit roots with multiple structural breaks.